MEDIA CANVAS SEBAGAI BAHAN AJAR IPA UNTUK MENINGKATKAN KUALITAS HASIL BELAJAR SISWA KELAS IV SEKOLAH DASAR - Marsela Luruk Bere (HINEF : Jurnal Rumpun Ilmu Pendidikan, 2023)
The era of the 21st century, which is synonymous with the era of the industrial revolution 4.0, is marked by various forms of paradigm change. The development of the modern world provides a new touch in the world of education that needs to be adjusted by educators and educated alike. Therefore, the aim of this research is to provide assistance to elementary science teachers in understanding the applications they want to apply in this study. One application that is often used is Canvas. This application is often used to design information using images, very unique icons that are able to convey information to readers in a simple and easily understood manner. Science material is one of the lessons that contains environmental pictures and calculations. Therefore, to improve the quality of learning for Grade IV elementary school students, Canvas media will be assisted as an interesting teaching material that is liked by elementary school students. Based on the results of research conducted using the interview method at 3 elementary schools, namely SDI Besterin, SDK Manumuti and SDK Betun I, namely before being given treatment the absorption and completeness values ​​were below the standard of 65% and 80% due to the lack of understanding of teachers in utilizing technology in the current era. After being given treatment using teaching materials designed with canvas the quality of learning is quite improved with absorption and completeness values ​​above average. This is because researchers provide special assistance to science teachers in operating canvas applications so that in applying them to students the teacher has total control.